Nucleoside/Nucleotide Analogues for the Treatment of Chronic Hepatitis B: A 3-Year Follow Up Study - Sulaiman, Andri Sanityoso; Hasan, Irsan; Lesmana, Cosmas Rinaldi A; Jasirwan, Chyntia Olivia M; Nababan, Saut Horas H.; Kalista, Kemal Fariz; Aprilicia, Gita; Gani, Rino Alvani (Jurnal Penyakit Dalam Indonesia, 2021)
Introduction. Chronic hepatitis B (CHB) is endemic in Indonesia, where it is usually treated with pegylated interferon and nucleoside/nucleotide analogs (NA). The aim of this study was to determine the efficacy of treating CHB infection among Indonesian patients with NA (lamivudine, telbivudine, and tenofovir) for a 3-year period.Methods. We retrospectively reviewed the records of patients with CHB infection attending the Hepatology Clinic Cipto Mangunkusumo during 2010-2013 period. Subjects with inclusion criteria were all patients aged above 18 years treated with NA for at least three years. The degree of liver stiffness, hepatitis B virus deoxyribonucleic acid (HBV-DNA), alanine aminotransferase (ALT) levels, and hepatitis B antigen (HBeAg) were assessed before and after 3-years therapy.Results. A total of 62 subjects were included in the study. Forty-eight patients (77%) were treated with telbivudine, 9 (15%) with tenofovir, and 5 (8%) with lamivudine. At baseline prior to the onset of therapy, 52 patients (84%) had a positive HBeAg test, 15 patients (24%) had F3 liver disease (advance fibrosis), and 36 (58%) had liver cirrhosis using transient elastography. At the end of the 3 year study period, median of liver stiffness significantly decline from baseline (14.5 (3.3 – 59.3) kPa to 6.7 (3.3 – 37.2) kPa, p = 0.001), HBV DNA load significantly decline (1.31 x 107 (2.0x106 – 1.0x108) copies/mL to 0 (0 – 1.7 x 107) copies/mL, p = 0.001), alanine aminotransferase (ALT) levels significantly decline (58 (11– 404) U/L to 27 (8-291) U/L, p = 0.001). Nevertheless, there were five patients (8%) who still had F3 liver disease, and 20 patients (32.3%) had F4 liver disease, 21 (34%) had detectable HBV-DNA, 17 (27%) had not achieved ALT normalization. From 52 patients with positive HBeAg 140| Jurnal Penyakit Dalam Indonesia | Vol. 8, No. 3 | September 2021Andri S. Sulaiman, Irsan Hasan, C.R.A. Lesmana, Chyntia O.M. Jasirwan, Saut Horas H. Nababan, Kemal F. Kalista, Gita Aprilicia, Rino A. Ganibaseline, there were 20 patients (39%) who had seroconversion to negative HBeAg after three year period.Conclusion. NA therapy resulted in a reduction level of fibrosis in CHB induced liver disease.